PENGELOLAAN GANGGUAN MOBILITAS FISIK MELALUI MOBILISASI DINI IBU POST PARTUM SECTIO SAESAREA (SC) DI RSUD dr.GUNAWAN MANGUNKUSUMO AMBARAWA - Ismawati, Eni; Eka Adimayanti (JURNAL ILMIAH NUSANTARA, 2025)
Childbirth through a cesarean section (CS) often results in physical mobility impairment in post-operative mothers. This condition is caused by surgical wound pain, weakness, and anxiety, which can hinder the recovery process. Early mobilization has been proven effective in accelerating this recovery. This descriptive case study aims to describe the management of physical mobility impairments through early mobilization in a post-C-section mother. The study employs a descriptive case study approach, with data collection through interviews, observations, physical examinations, and documentation. Data validity was tested through peer review and triangulation of sources (patient, nurse, and family). The results showed that the patient (Mrs. I) experienced complaints of fear of movement, weakness, and dependence. The primary nursing diagnosis was physical mobility impairment related to the effects of anesthesia. The interventions applied included bed rest care, ambulation exercise therapy, and gradual self-care assistance. Early mobilization was successfully implemented, with the patient able to move sideways, sit, and walk independently. This success was supported by effective communication and family support. After three days of intervention, Mrs. I's physical mobility impairment was partially resolved, marked by improved mobility and reduced pain. This study is expected to serve as a reference for nurses, hospitals, and the community on the importance of early mobilization.